Measuring and applying the PAKSERV service quality construct: Evidence from a South African cultural context - Graham Saunders, Stephen (Managing service quality, 2008)
Purpose - The purpose of this paper is to examine the PAKSERV service quality measure in a South African cultural context. Design/methodology/approach - In order to test and confirm the dimensionality of the PAKSERV service quality construct a confirmatory factor analysis (CFA) was used. The data were collected through a survey of over 300 Black South African banking customers. Findings - The results of the CFA confirmed that PAKSERV is a valid measure of service quality in a South African cultural context, consisting of six dimensions: tangibility, reliability, assurance, sincerity, personalisation and formality. Research limitations/implications - A major limitation of this study is that PAKSERV was only validated for the banking sector. To ensure validity across a variety of industries and cultural contexts, further replication would be needed. Practical implications - By measuring and evaluating service quality dimensions that are culturally relevant to customers, marketing managers can focus on the dimensions of service quality that are not adequately captured in the SERVQUAL instrument. The paper recommends three useful managerial applications of the service quality construct. The findings are particularly valuable to international services managers who what to move away from a single international service strategy and embrace a flexible service delivery strategy that is culturally sensitive. Originality/value - The study contributes by providing further validation for the PAKSERV service quality measurement scale. This is also one of the few studies to test and confirm a culturally sensitive service quality construct in Africa. Furthermore, the study questions the notion that the PAKSERV measurement scale is culturally specific and argues that PAKSERV should be seen as a generic measurement scale that can be used across a variety of countries and cultural contexts. [PUBLICATION ABSTRACT]